Enhancing Resilience and Justice in Climate Adaptation Laws. Issue 1 (4th December 2018) - Wenta, Joseph; McDonald, Jan; McGee, Jeffrey S.
Abstract: Resilience thinking – an approach for understanding and managing change – is increasingly central to climate change adaptation law and policy. Yet the influence of adaptation law and policy on the distribution of climate impacts is often overlooked in studies of socio-ecological resilience to climate change. This article demonstrates how environmental justice scholarship helps to address this gap in the literature relating to adaptation law and resilience. Drawing on existing literature, the article identifies four principles to promote resilience and justice through climate adaptation laws. Climate adaptation laws must (i) prepare for, and respond to, change; (ii) address the distributive effects of climate change and adaptation; (iii) promote participation in adaptation processes; and (iv) cross sectors and scales. Each criterion can be implemented in part through existing legal processes, but might also be further supported by incremental law reform. Developing both resilience and justice dimensions will enhance the effectiveness of adaptation laws in addressing climate impacts.